Comparing analytically propulsion by pitching and heaving flexible foils near the first two natural modes - Fernández-Feria, Ramón (Cambridge University Press, 2025)
An analytical formulation is provided that describes the first two natural modes of the fluid–structure interaction of an incompressible current with a pitching and heaving flexible plate. The objective is twofold: first, to present a general derivation of analytical expressions for the lift, moment and the flexural moments exerted by an inviscid flow on a pitching and heaving plate whose deformation is general enough that the coupling of the flexural moments with the structural equations allows solving analytically the first two natural modes of the system; second, to analyse the propulsion performance of the foil when actuated near the first two natural frequencies. For the second purpose, one also needs the thrust force generated through the motion and the general deformation of the foil considered, which is analytically derived using the linearized vortex impulse theory, extending and systematizing previous works. The analytical expressions, once viscous effects are taken into consideration through nonlinear transverse damping and offset drag coefficients, are compared with small-amplitude available experimental data, discussing their limitations. It is found that low stiffness pitching and heaving are quite different, with a pitching flexible foil only generating thrust near the second resonant frequency, whereas heaving always generates thrust, with the maximum slightly below the second natural frequency. Maximum thrust for large stiffness pitching is around the first natural frequency. The maximum efficiency occurs at frequencies close to the first natural mode if the foil is sufficiently rigid, but it is not related to the natural frequencies as the rigidity decreases.
Keywords: Deformaciones (Mecánica); Flexión (Mecánica); Flow-structure interactions; Propulsion; Swimming/flying